Caracterización de parámetros para el diseño hidráulico de redes de riego a presión y redes de abastecimiento, con empleo de software de aplicación - Robalino Quizhpe, Byron Gonzalo (2018)
Abstract: The present work of investigation treats on the hydraulic design of networks to pressure. It will analyze specifically a network of irrigation and a network of supply of drinkable water, with the aim to characterize the hydraulic parameters like the pressure, velocity, and flow. The design was applied to the existing networks of the San Pedro de la Bendita parish in the province of Loja. The irrigation network has been designed with irrigation on demand and hydraulic parameters are established based on the Spanish and Ecuadorian technical prescriptions. On the other hand, the supply network is governed by parameters of current Ecuadorian regulations. Also, a branched topology was maintained in both networks and later it was modeled in software to validate the results of the hydraulic design. It was possible to observe the considerable difference that exists in the hydraulic dimensioning of these networks, although the design procedure is the same, the hydraulic parameters have design ranges with important particularities. Finally, it was possible to structure a manual for the design of pressure networks, obtaining with this a document of support for those interested in this area.